Cardiac effects of echinocandins in endotoxemic rats - Koch, Christian; Wolff, Matthias; Henrich, Michael; Weigand, Markus A.; Lichtenstern, Christoph; Uhle, Florian (Antimicrobial agents and chemotherapy, 2016)
Echinocandins are known as effective and safe agents for the prophylaxis and treatment of different cohorts of patients with fungal infections. Recent studies revealed that certain pharmacokinetics of echinocandin antifungals might impact clinical efficacy and safety in special patient populations. The aim of our study was to evaluate echinocandin-induced aggravation of cardiac impairment in septic shock. Using an in vivo endotoxemic shock model in rats, we assessed hemodynamic parameters and time to hemodynamic failure (THF) after additional central-venous application of anidulafungin (2.5 mg/kg of body weight [BW]), caspofungin (0.875 mg/kg BW), micafungin (3 mg/kg BW), and control (0.9% sodium chloride). In addition, echinocandin-induced cytotoxicity was evaluated in isolated rat cardiac myocytes. THF of the animals in the caspofungin group (n = 7) was significantly reduced compared to that in the control (n = 6) (136 min versus 180 min; P = 0.0209). The anidulafungin group (n = 7) also showed a trend of reduced THF (136 min versus 180 min; log-rank test P = 0.0578). Animals in the micafungin group (n = 7) did not show significant differences in THF compared to those in the control. Control group animals and also micafungin group animals did not show altered cardiac output (CO) during our experiments. In contrast, administration of anidulafungin or caspofungin induced a decrease in CO. We also revealed a dose-dependent increase of cytotoxicity in anidulafungin- and caspofungin-treated cardiac myocytes. Treatment with micafungin did not cause significantly increased cytotoxicity. Further studies are needed to explore the underlying mechanism.